The complete chloroplast genome sequence of the Cucurbita pepo L. (Cucurbitaceae) - Chen Zhang; Qianglong Zhu; Shi Liu; Peng Gao; Zicheng Zhu; Xuezheng Wang; Feishi Luan (Mitochondrial DNA. Part B. Resources, 2018)
Cucurbita pepo is an important economic plant cultivated widely in the world. The complete chloroplast genome sequence of C. pepo is reported here. The genome is 157,343 bp in length and exhibits a typical quadripartite structure of the large (LSC, 87,970 bp) and small (SSC, 18,167 bp) single-copy regions, separated by a pair of inverted repeats (IRs, 25,603 bp). A total of 131 genes were predicted including 85 protein-coding genes, eight rRNA genes and 38 tRNA genes. Further, phylogenetic analysis showed that C. pepo were closely related to other species in the family Cucurbitaceae. The complete chloroplast genome of C. pepo would be taken as a useful molecular tool for species discrimination, taxonomy, and phylogenetic relationships in the family Cucurbitaceae.